The Effects of Fuel Price Fluctuation on Household Income in Malaysia - Rahim N.A.; Yusoff Y.S.; Ibrahim M.S. (Institute for Mathematical Research (INSPEM), Universiti Putra Malaysia, 2024)
Indexed by WOS/MyCite